Ultra‐Broadband Strong Electromagnetic Interference Shielding with Ferromagnetic Graphene Quartz Fabric. Issue 30 (22nd June 2022) - Xie, Yadian; Liu, Shan; Huang, Kewen; Chen, Bingbing; Shi, Pengcheng; Chen, Zhaolong; Liu, Bingzhi; Liu, Kaihui; Wu, Zhiqiang; Chen, Ke; Qi, Yue; Liu, Zhongfan
Abstract: Flexible electromagnetic interference (EMI) shielding materials with ultrahigh shielding effectiveness (SE) are highly desirable for high‐speed electronic devices to attenuate radiated emissions. For hindering interference of their internal or external EMI fields, however, a metallic enclosure suffers from relatively low SE, band‐limited anti‐EMI responses, poor corrosion resistance, and non‐adaptability to the complex geometry of a given circuit. Here, a broadband, strong EMI shielding response fabric is demonstrated based on a highly structured ferromagnetic graphene quartz fiber (FGQF) via a modulation‐doped chemical vapor deposition (CVD) growth process. The precise control of the graphitic N‐doping configuration endows graphene coatings on specifically designable quartz fabric weave with both high conductivity (3906 S cm −1 ) and high magnetic responsiveness (a saturation magnetization of ≈0.14 emu g −1 under 300 K), thus attaining synergistic effect of EMI shielding and electromagnetic wave (EMW) absorption for broadband anti‐EMI technology. The large‐scale durable FGQF exhibits extraordinary EMI SE of ≈107 dB over a broadband frequency (1–18 GHz), by configuring ≈20 nm‐thick graphene coatings on a millimeter‐thick quartz fabric. This work enables the potential for development of an industrial‐scale, flexible, lightweight, durable, and ultra‐broadband strong shielding material in advanced applications of flexible anti‐electronic reconnaissance, antiradiation, and stealthy technologies. Abstract : A novel broadband, strong electromagnetic intereference (EMI) shielding response fabric based on highly structured ferromagnetic graphene quartz fibers is demonstrated, which combines high conductivity and ferromagnetism to attain a synergistic effect for EMI shielding and electromagnetic wave (EMW) absorption, along with the specific woven superstructure of the fabric to introduce the additional multiple reflections and multichannel absorption of EMWs.